INOVASI KEPEMIMPINAN KEPALA MADRASAH KREATIF DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH - ja'far ja'far (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2019)
This knowledge has a purpose to know the problems of the headmaster to make the innovation and creation to increase the education quality. The method of knowledge that used is qualitative, the presentation method is descriptive Analysis, also designed with the literature phenomenology that allow some literature related to the study of headmaster problems to make the innovation and creation to increase the education quality such as low support from the parents and society about the finance like the parents feel exception when the school fee increase, the minimally finance a facility, the inappropriate teacher with the qualification also minimally teachers commitment. So, it can be the problem of the headmaster to make innovation and creation to increase education quality. The solution of those problems such as keep on giving the understanding to the parents and society that what headmaster and teachers do have a purpose to their students. They use school finance efficiently. For better facilities, the headmaster tried to get the assist from the government to complete the school facilities. And for the inappropriate teacher with the qualification, the institute must allow the teachers to participate in the training or study at university. And for lower commitment, the headmaster can give the motivation so that the teacher will have the motivation to be better.